Adenomatoid Odontogenic Tumour Associated with Dentigerous Cyst: Case Report with Literature Review - Pradipta Ramgonda Patil; Hirkani Attarde; Priyanka Prakash Kamble; Sangeeta Patankar; Gokul Sridharan (Journal of Clinical and Diagnostic Research, 2021)
Adenomatoid Odontogenic Tumour (AOT) is a relatively uncommon benign odontogenic tumour composed of odontogenic epithelium in a variety of histoarchitectural patterns. Conventional AOT is predominantly seen in females in second decade of life exhibiting predilection for anterior region of maxilla. Very few cases of AOT associated with dentigerous cyst have been reported till date. The present case is unique associated with an impacted lower first premolar in the front region of the mandible of an 18-year-old female patient. The patient reported to the institute with gradually increasing swelling. The orthopantomogram revealed a unilocular radiolucency with displaced premolar. Histopathological examination confirmed 4×2.5×2 cm lesion in dimension, brownish black in colour, firm in consistency with a smooth surface grossly while cut surface revealed a cystic lumen with an impacted premolar embedded into the lining, cystic wall being nodular. Microscopic evaluation revealed a well encapsulated lesion with a thin 2-3 cell layered non keratinised stratified epithelial lining in patterns such as nests, rosette like structures and duct like structures. Thus the diagnosis of AOT arising from dentigerous cyst was confirmed. Patient's six month follow-up was uneventful. Literature search of similar cases with the review of hypothesised aetiopathogenesis is discussed in brief. The available data can help researchers resolve the uncertainty whether the AOT derived from dentigerous cyst could represent a distinct hybrid variety.